PENGARUH FASHION INFLUENCER, PROMOSI DIGITAL, DAN PERSEPSI GAYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK STREETWEAR OLEH GENERASI Z - Vina Dwi Yanti; Haryanto Tanuwijaya; Sri Suhandiah (Universitas Sarjanawiyata Tamansiswa, 2026)
This study purposes to analyze the influence of fashion influencers, digital promotion, and style perception on streetwear purchase decisions among Generation Z. The research employed a quantitative approach using a survey method. A five-point Likert scale was used in an online survey to gather data from 103 Generation Z respondents in Surabaya who actively use social media and have purchased streetwear products within the last six months. Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4 software was used to analyse the data.The findings indicate that fashion influencers, digital promotion, and style perception have a positive and significant effect on purchase decisions. Digital promotion shows the strongest influence, followed by fashion influencers and style perception. The coefficient of determination (R²) value of 0.712 indicates that 71.2% of the variance in purchase decisions is explained by the three independent variables, while the predictive relevance (Q²) value of 0.478 demonstrates that the model has good predictive capability. These findings indicate that streetwear purchase decisions among Generation Z are influenced by the integration of digital promotion strategies, influencer credibility, and consumers’ style perception aligned with their self-identity.